Electronic Word-Of-Mouth (E-Wom) Model and Consumer Decisions on Pantai Cermin Tourism - Rivai, Ahmad; Amalia, Fiqrida; Chaniago, Sabaruddin; Martin, Martin; Nasib, Nasib (International Journal of Science, Technology & Management, 2022)
The main objectives of this research are to study the factors that influence Electronic Word-Of-Mouth (E-Wom) and consumer decisions and to formulate the Electronic Word-of-Mouth (E-Wom) model and consumer decisions to travel on the beach. Deli Serdang Mirror. This study uses descriptive analysis, both qualitative and quantitative. Data analysis with statistics used is the Structural Equation Modeling (Structural Equation Modeling). Based on the analysis and discussion, it is concluded that there is a significant influence of Service Quality on E-WOM. There is a significant effect of Price on E-WOM. There is a significant effect of Service Quality on Purchase decisions. There is a significant effect of E-WOM on Purchase decisions. There is a significant effect of E-WOM on Purchase decisions. There is a significant influence of Service Quality on Purchase decisions through E-WOM. And there is a significant effect of Price on Purchase decisions through E-WOM